AIDS SOCIAL EXPENDITURES, POVERTY AND INEQUALITY IN TIME OF COVID-19 PANDEMIC IN INDONESIA - Anwar, Syaiful; Yudaruddin, Rizky; Naprida, Dewi; Rai Wibowo, Bagus; Lesmana, Dadang (PLANNING MALAYSIA, 2024)
The research investigates the correlation between social aid expenditure and poverty, and inequality across 34 Indonesian provinces from 2004 to 2022. Utilizing the two-step Generalized Method of Moments (GMM) estimate, it examines the impact of social aid expenditure on poverty rates and the Gini coefficient during the COVID-19 pandemic. Results show a significant decrease in the proportion of the impoverished population due to social aid expenditure, with minimal effects on inequality. The study highlights a substantial increase in both poverty and inequality during the pandemic, particularly in rural and urban areas. Analyzing the relationship between social welfare spending and COVID-19 impact reveals a positive influence on disadvantaged populations and inequality in Indonesian provinces. This underscores the need for a comprehensive review of social aid programs, especially amidst COVID-19 challenges.